Five new species of the land snail genus Landouria Godwin-Austen, 1918 (Gastropoda, Camaenidae) from northeastern Thailand, with note on genitalia and radula morphology of Landouria diplogramma (Möllendorff, 1902) - Nahok, Benchawan; Tumpeesuwan, Sakboworn; Tumpeesuwan, Chanidaporn (European Journal of Taxonomy, 2021)
Five new species of the terrestrial snail genus Landouria Godwin-Austen, 1918 (Camaenidae) are described from northeastern Thailand, based on shell features, radular morphology, genital anatomy, and DNA sequence data: Landouria circinata sp. nov., L. tuberculata sp. nov., L. trochomorphoides sp. nov., L. chloritoides sp. nov., and L. elegans sp. nov. These species are phylogenetically well separated from each other by mtDNA phy-logeny and COI sequence divergences of 0.073–0.156. The record of Thaitropis Schileyko, 2004 (currently synonymized with Landouria) in Thailand is re-interpreted as referring to L. diplogramma (Möllendorff, 1902) comb. nov.